How to Cheat in Adobe Flash CS5 - Georgenes, Chris (Routledge, 2012)
Need to solve problems quickly to develop creative projects to time and to budget? Want to hone your Flash skills so you can concentrate on your animation? Then How to Cheat in Flash is for you! Chris Georgenes shows how to work from the problem to the solution - from the viewpoint of an animator who has been commissioned to create a job and is working to a deadline and to a budget. With his in-depth knowledge of the little-known secrets used by the pros to produce creative, professional animations, Chris is the go-to guru for designers and animators who want to create great animation, applications or motion design with Flash. Fully updated for CS5, How to Cheat in Flash CS5, is a goldmine of artistic inspiration, timesaving practical tips, tricks and step-by-step workthroughs that you'll wonder how you survived without it. Each techniques is designed as a double-page spread so you can prop the book up behind your keyboard or next to your monitor as a visual reference while working alongside it. Many of these workthroughs are real-world client projects, with the source files supplied for you to open and explore. With these real-life professional projects you'll discover how to: bring objects to life with cool motion effects, make it rain, snow or set your world ablaze, develop flash mobile applications and many more tips and tricks not found anywhere else!